1995
DOI: 10.1002/ajim.4700280102
|View full text |Cite
|
Sign up to set email alerts
|

Establishment size and risk of occupational injury

Abstract: For many years, the annual survey of occupational injuries and illnesses by the Federal Bureau of Labor Statistics (BLS) has consistently reported, without explanation, that injury rates in the smaller establishments (< 50 employees) are substantially lower than those for midsize establishments (100-499 employees). Also during those years, a remarkable increase has been reported in the injury rate in large companies, following the imposition of stiff fines for failure to keep required injury records. The rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 10 publications
3
51
1
Order By: Relevance
“…Twelve of the ergonomic and physical-agent hazards occurred most often in establish ments of this size. These findings not only replicate the results for occupationally-related injuries obtained by Oleinick et al (1995), but indicate that the lower rates of occupational injuries experienced among small establishments compared to larger establishments may result, at least to a substantial degree, from lower hazard exposure, and not just to under-reporting as Oleinick and colleagues had surmised (1995).…”
Section: Exposure Probabilities By Establishment Sizesupporting
confidence: 78%
See 1 more Smart Citation
“…Twelve of the ergonomic and physical-agent hazards occurred most often in establish ments of this size. These findings not only replicate the results for occupationally-related injuries obtained by Oleinick et al (1995), but indicate that the lower rates of occupational injuries experienced among small establishments compared to larger establishments may result, at least to a substantial degree, from lower hazard exposure, and not just to under-reporting as Oleinick and colleagues had surmised (1995).…”
Section: Exposure Probabilities By Establishment Sizesupporting
confidence: 78%
“…The rationale for this assumption is that small establishments, compared to large establishments, have poorly-organized employees (i.e., union representatives are not available to intercede on employees' behalf to correct health and safety problems) and cannot afford adequate safety and health programs. Prior analysis of occupationally-related injury and illness reporting data, however, found that small establish ments (<50 employees) have significantly lower injury and illness rates than establishments employing between 100 and 499 workers (Oleinick, Gluck, & Guire, 1995). These researchers, however, attribute the lower rates for small establishments to underreporting of illnesses and injuries.…”
Section: Exposure Probabilities By Establishment Sizementioning
confidence: 77%
“…We also know that smaller establishments are less likely to engage in safety training. Safety training programs were reported by 28.3 percent of small (8-99) plants, 53.2 percent of those with 100-499, and 80.5 percent of those with 500 or more workers (Oleinick, Gluck, and Guire, 1995). The cost of training would presumably be lower at larger establishments and firms because of the potential for economies of scale.…”
Section: Costs and Benefits Might Be Related To Sizementioning
confidence: 99%
“…As for the underreporting hypothesis, Oleinick, Gluck, and Guire (1995) examined workplaces in Michigan to see whether smaller workplaces tended to have fewer risk factors than did larger workplaces. They found the opposite.…”
Section: Underreporting and Sizementioning
confidence: 99%
“…Occupational characteristics (ie, job permanency, usual weekly hours worked, physical demands, and number of employees in the organization) provided information about working conditions that may be associated with the risk for a work injury. Those new to a work situation, such as those starting a job, who work a greater number of hours, or who work in large organizations have been found in previous research to have increased risks of work injury (29)(30)(31)(32)(33).…”
Section: Outcome and Predictor Variablesmentioning
confidence: 99%